2017
DOI: 10.1161/circresaha.116.310557
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenic Mechanisms of Human CD34 + Stem Cell Exosomes in the Repair of Ischemic Hindlimb

Abstract: Rationale Paracrine secretions appear to mediate therapeutic effects of human CD34+ stem cells locally transplanted in patients with myocardial and critical limb ischemia as well as in animal models. Earlier, we had discovered that paracrine secretion from human CD34+ cells contains pro-angiogenic, membrane-bound nano-vesicles called exosomes (CD34Exo). Objective Here, we investigated the mechanisms of CD34Exo-mediated ischemic tissue repair and therapeutic angiogenesis by studying their miRNA content and up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
208
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(217 citation statements)
references
References 36 publications
8
208
0
1
Order By: Relevance
“…Thus, elevations in CD34+ MPs observed with in the older groups may be indicative of chronic low-grade inflammation associated with older age. Alternatively, CD34+ exosomes have been found in vitro to contain angiogenesis-promoting miRNAs (Sahoo & Losordo, 2014; Mathiyalagan et al , 2017). Although the size and mechanisms of release differ between exosomes and MPs, potential similarities in cargo between the two extracellular vesicles suggest that perhaps the elevations in CD34+ MPs are serving in a compensatory capacity to offset the elevations in CD62E+ MPs also associated with older age.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, elevations in CD34+ MPs observed with in the older groups may be indicative of chronic low-grade inflammation associated with older age. Alternatively, CD34+ exosomes have been found in vitro to contain angiogenesis-promoting miRNAs (Sahoo & Losordo, 2014; Mathiyalagan et al , 2017). Although the size and mechanisms of release differ between exosomes and MPs, potential similarities in cargo between the two extracellular vesicles suggest that perhaps the elevations in CD34+ MPs are serving in a compensatory capacity to offset the elevations in CD62E+ MPs also associated with older age.…”
Section: Discussionmentioning
confidence: 99%
“…17 Recent research also revealed that knockdown of miR-126-3p from CD34 Exo abolished angiogenic activity and beneficial function both in vitro and in vivo. 18 These findings prompted us to investigate the therapeutic effect of miR-126-3p overexpression on heart function in ICM models.…”
Section: Discussionmentioning
confidence: 99%
“…10, 11 Based on work conducted by Jiang, it was also reported that human endometrial stem cell transplantation can improve cardiac function by regulating cytokine secretion. 12 The altered cytokine levels in peripheral blood mononuclear cells (PBMCs) were also found to correlate with the progression and severity of heart disease.…”
mentioning
confidence: 99%
“…Although EVs are produced by many cell types, EVs from multiple progenitor cell lineages are released into the peripheral circulation and target distant sites with potent pro‐angiogenic stimuli. Mathiyalagan et al have recently shown that human CD34+ cell‐derived exosomes injected into the ischemic hindlimb of mice improved limb perfusion via EC uptake of miRNA‐126‐3p that suppressed expression of the sprouty‐family gene, SPRED1, and simultaneously upregulated VEGF, ANGF1, ANG2, and MMP9 expression . ECFC‐derived EVs incorporate into ECs via interaction with α4 and ÎČ1 integrins, and stimulate angiogenesis via delivery of mRNA associated with eNOS production and PI3K/AKT pathway .…”
Section: What Has Gone Wrong and What Can We Do Better?mentioning
confidence: 99%